Cooperative TRAIL production mediates IFNα/Smac mimetic-induced cell death in TNFα-resistant solid cancer cells - Roesler, Stefanie (Oncotarget, 2016)
Smac mimetics antagonize IAP proteins, which are highly expressed in several cancers. Recent reports indicate that Smac mimetics trigger a broad cytokine response and synergize with immune modulators to induce cell death. Here, we identify a differential requirement of TRAIL or TNFα as mediators of IFNα/Smac mimetic-induced cell death depending on the cellular context. Subtoxic concentrations of Smac mimetics cooperate with IFNα to induce cell death in various solid tumor cell lines in a highly synergistic manner as determined by combination index. Mechanistic studies show that IFNα/BV6 cotreatment promotes the formation of a caspase-8-activating complex together with the adaptor protein FADD and RIP1. Assembly of this RIP1/FADD/caspase-8 complex represents a critical event, since RIP1 silencing inhibits IFNα/BV6-induced cell death. Strikingly, pharmacological inhibition of paracrine/autocrine TNFα signaling by the TNFα scavenger Enbrel rescues HT-29 colon carcinoma cells, but not A172 glioblastoma cells from IFNα/BV6-induced cell death. By comparison, A172 cells are significantly protected against IFNα/BV6 treatment by blockage of TRAIL signaling through genetic silencing of TRAIL or its cognate receptor TRAIL receptor 2 (DR5). Despite this differential requirement of TNFα and TRAIL signaling, mRNA and protein expression is increased by IFNα/BV6 cotreatment in both cell lines. Interestingly, A172 cells turn out to be resistant to exogenously added recombinant TNFα even in the presence of BV6, whereas they display a high sensitivity towards TRAIL/BV6. In contrast, BV6 efficiently sensitizes HT-29 cells to TNFα while TRAIL only had limited efficacy. This demonstrates that a differential sensitivity towards TRAIL or TNFα determines the dependency on either death receptor ligand for IFNα/Smac mimetic-induced cell death. Thus, by concomitant stimulation of both death receptor systems IFNα/Smac mimetic combination treatment is an effective strategy to induce cell death in TNFα- or TRAIL-responsive cancers.